Vibrational spectroscopy in diagnosis and screening - Severcan, Feride; Haris, P. I. (Parvez I.) (Advances in biomedical spectroscopy, 2012)
In recent years there has been a tremendous growth in the use of vibrational spectroscopic methods for diagnosis and screening. These applications range from diagnosis of disease states in humans, such as cancer, to rapid identification and screening of microorganisms. The growth in such types of studies has been possible thanks to advances in instrumentation and associated computational and mathematical tools for data processing and analysis. This volume of Advances in Biomedical Spectroscopy contains chapters from leading experts who discuss the latest advances in the application of Fourier transform infrared (FTIR), Near infrared (NIR), Terahertz and Raman spectroscopy for diagnosis and screening in fields ranging from medicine, dentistry, forensics and aquatic science. Many of the chapters provide information on sample preparation, data acquisition and data interpretation that would be particularly valuable for new users of these techniques including established scientists and graduate students in both academia and industry.